PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA - A Andriani Yunus; Asdar Dollo; Abdul Rahman (Tautologi: Journal of Mathematics Education, 2025)
Mathematical communication skills are an essential competence in mathematics learning because they enable students to express ideas, explain reasoning, and represent concepts logically through symbols, writing, and diagrams. However, many students still experience difficulties in articulating mathematical thinking systematically due to teacher-centered learning that provides limited opportunities for discussion and written reflection. This condition necessitates the implementation of more interactive and collaborative learning models, one of which is the Think Talk Write (TTW) cooperative learning model. This study aims to analyze the effect of implementing the TTW model on the mathematical communication skills of eighth-grade junior high school students. The research employed a quantitative approach with a one-group pretest–posttest pre-experimental design. The sample was determined through cluster sampling involving 21 students of class VIII A. The instrument consisted of a validated essay test measuring mathematical communication skills. Data were analyzed using descriptive and inferential statistics, including a normality test and paired samples t-test at a significance level of 0.05. The results revealed a significant improvement in students’ mathematical communication skills after the implementation of the TTW model. The mean score increased from 64.86 on the pretest to 83.52 on the posttest, accompanied by a shift in ability categories from predominantly “moderate” to “high” and “very high.” The t-test produced a significance value of 0.000 (p < 0.05), indicating a meaningful difference between pre- and post-treatment results. Furthermore, the decrease in standard deviation suggests a reduction in ability gaps among students. Pedagogically, the effectiveness of TTW is supported by the integration of the think, talk, and write stages, which facilitate independent thinking, collaborative discussion, and structured written reasoning. Therefore, the TTW model is proven effective and recommended for enhancing students’ mathematical communication skills in mathematics learning.